2008
DOI: 10.1177/1557988308322815
|View full text |Cite
|
Sign up to set email alerts
|

Success with Men's Educational Group Appointments (MEGA): Subjective Improvements in Patient Education

Abstract: Men have a higher age-adjusted death rate from many of the leading causes of death, compared with women. Avoidance of health care and unhealthy behavior contribute to premature death among men. The Lahey Clinic recently initiated a program, the Men's Educational Group Appointment (MEGA), which capitalizes on the potential benefits of group dynamics in an effort to educate men about preventative health. We hypothesized that putting men into a group setting for the educational portion of the visit would improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Conducting MEGA workshops in rural Nicaragua provided an environment in which men appeared to feel comfortable participating, in spite of belonging to a culture where machismo often precludes men from seeking health care. This finding was commensurate with some investigations in the United States ( Campbell et al, 2009 ; Campbell & Gosselin, 2007 ). During earlier visits to Nicaragua, it was observed that many men, who had made the journey with their families to the health post, not receive any care themselves.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Conducting MEGA workshops in rural Nicaragua provided an environment in which men appeared to feel comfortable participating, in spite of belonging to a culture where machismo often precludes men from seeking health care. This finding was commensurate with some investigations in the United States ( Campbell et al, 2009 ; Campbell & Gosselin, 2007 ). During earlier visits to Nicaragua, it was observed that many men, who had made the journey with their families to the health post, not receive any care themselves.…”
Section: Discussionsupporting
confidence: 93%
“…Such programs leverage the fact that group dynamics can be effective in behavior change programs, such as weight loss and abstinence from alcohol ( Hogan, Linden, & Najarian, 2002 ; Vederhus & Kristensen, 2006 ). In one men’s educational group appointment (MEGA) model, high patient satisfaction was reported; patients reported increased education compared with traditional appointments, and felt more at ease attending an appointment in a group ( Campbell & Gosselin, 2007 ; Campbell, Shaw, & Gosselin, 2009 ). The problem of hypertension in Nicaraguan men was felt to be a prime target for initiation of a group-based, male-oriented, peer leadership teaching initiative.…”
Section: Introductionmentioning
confidence: 99%
“…The interprofessional team plays a prominent role in SMAs across the literature, including nurses, nutritionists, NPs, pharmacists, physical therapists, PAs, primary healthcare coordinators and nurse midwives [7, 8, 14, 34, 52]. Despite these reallocation of tasks, roles, and resources, SMAs demonstrate efficacy and feasibility across a wide range of healthcare systems [39, 53].…”
Section: Discussionmentioning
confidence: 99%
“…Honoring adult learning strategies often requires nonclinical skill sets for interdisciplinary care clinicians [38]; yet, few studies focused on interprofessional practice despite widespread presence across differing SMA models. SMAs emphasize patient empowerment through peer accountability, socialization, and appreciation of local cultural context as well as patients’ familiarity and comfort with the setting [40, 43, 53]. Engaging group members in the design of these SMAs can maximize responsiveness to cultural context and acceptability of the model [43].…”
Section: Discussionmentioning
confidence: 99%
“…There are existing health promotion programs that target men, such as The ManMOT, 25 Men's Sheds, 26 Men's Educational Group Appointments (MEGA), 27 and PIT-STOP. 28 However, implementation of these programs has met with many challenges.…”
Section: Health Innovation For Men's Health Promotionmentioning
confidence: 99%